Japanese Verbs Meaning Extention in Minna No Nihongo II: A Semantic and Contextual Review - melati br sitepu (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2025)
This study aims to analyze the phenomenon of polysemy in Japanese verbs found in the textbook Minna no Nihongo II. Polysemy refers to a semantic phenomenon in which a single word carries multiple related meanings. The research focuses on identifying the basic meanings and extended meanings of polysemous verbs and explaining the semantic relationships between them within various sentence contexts. This study employs a descriptive qualitative method using distributional and compositional analysis techniques as outlined by Mahsun. Data were collected through an observation and note-taking technique, with Minna no Nihongo II serving as the primary data source. The analysis revealed ten polysemous verbs: aruある , yasumu休む, hairu入る, deru出る, kiru切る, oshieru教える, kiku聞く, miru見る, toru取る, and ochiru落ちる. Each verb exhibits semantic shifts driven by context, including metaphorical, metonymic, and synecdochic processes. These shifts are influenced by grammatical structures, communicative functions, and socio-cultural factors. The findings highlight the pedagogical importance of understanding polysemous verbs in Japanese language acquisition, especially for non-native learners.